Asymmetry of Information on Umrah Pilgrim Services from Foucault's Perspective - Firdausiyah, Salsabila; Jaharuddin, Jaharuddin (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2025)
This study reveals that information asymmetry in Umrah pilgrimage services arises from disparities in access to and control over information between travel agencies and pilgrims. These disparities are driven by a lack of transparency regarding costs, facilities, and schedules, exacerbated by the limited prior knowledge of the pilgrims. This asymmetry manifests in the form of miscommunication, withholding, and delays in information dissemination. Based on Michel Foucault’s theory of power relations, the control of information serves as a tool to influence pilgrims’ behavior and create an unequal dependency. To address this issue, the study recommends improving transparency in service processes, educating pilgrims about their rights and responsibilities, enhancing service planning, and increasing the professionalism of travel agencies.